Management of metastatic renal cell carcinoma in patients with poor prognosis - Bullock, Andrea (Dove Medical Press, 2010)
An improved understanding of renal cell carcinoma (RCC) biology has translated into major advances in the treatment of patients with metastatic RCC in recent years. Clinical and pathologic criteria can be used to identify RCC patients with poor prognoses. Such patients, however, are often excluded from the cancer clinical trials that guide treatment recommendations. This article reviews available information on the management of patients with metastatic RCC and poor risk features, focusing on the role of vascular endothelial growth factor (VEGF) pathway and mammalian target of rapamycin (mTOR) inhibitors. While patients with poor risk features have a more guarded outcome, treatment with temsirolimus has produced meaningful improvements in overall survival for this population. Definitive phase III trial data are lacking for the VEGF pathway inhibitors in patients with poor prognostic features. However, available data suggest that such patients tolerate VEGF pathway blockade reasonably well and are likely to achieve some benefit relative to treatment with interferon. Ongoing translational research efforts may help to define novel treatment approaches specific for patients with metastatic RCC and poor prognostic features.